UJI PERBANDINGAN EFEKTIVITAS ANTIDIABETES EKSTRAK POLISAKARIDA DAN SENYAWA POLIFENOL ALGA COKLAT (Sargassum sp.) PADA MENCIT YANG DIINDUKSI ALOKSAN - Agung Giri Samudra; Fathur Sani K; Moniq Chintama (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Diabetes is one of the most common diseases in the world. So there is an effort to prevent or treat the disease. As brown algae (Sargassum sp.) Contains polysaccharides that regulate sugar intake in the body, and polyphenols act as antioxidants that can stimulate insulin secretion in pancreatic β cells. This study aims to determine the effectiveness of Antidiabetes Polysaccharide Extract and Brown Algae Polifenol Compounds (Sargassum sp) On Alloxaninduced Mice. The test animals were grouped into 4 groups I (CMC 1%), Group II (Glibenclamide 0.52mg / 20grBB), Group III (5mg / 20grBB polyphenol extract), Group IV (5mg / 20grBB polysaccharide extract). Blood glucose was measured using Easy touch glucometer on days 0, 3, 7, 14, 21, and 28. Analyze data using one-way ANOVA, followed by LSD test. The percentage decrease in blood glucose level in positive control, polyphenol extract and polysaccharide were 42,86%, 58,12%, and 54,20%. Statistically, the polyphenolic extract and the brown algae polysaccharide lower the blood glucose level significantly compared with the negative control (p≤0,05). Decreased blood glucose in polyphenol extracts and polysaccharides showed statistically significant differences